The Female Voice in Gradnik’s Love Poetry and in Marguerite Burnat-Provins’s Le Livre pour toi - Žerjal Pavlin, Vita (Slavia Centralis, 2024)
In several of the poems with a female lyrical subject from Alojz Gradnik’s first three collections (Padajoče Zvezde, Pot Bolesti, De Profundis), a strong erotic desire of a woman is expressed. Female erotic sensuality is also essentially defined in the collection of poems Le Livre Pour Toi (1907) by the French-Swiss writer, poet and painter Marguerite Burnat-Provins, translated by Gradnik and published in 1923 under the title Knjiga za Tebe. It is not to say that this French book had a direct influence on Gradnik’s love poems. The aim of this paper is therefore to make a more detailed inquiry into the existing literary-historical comparison of the literarisation of love by both authors, namely by analysing the concept of love and the position of women in the amorous relationship.
Keywords: Alojz Gradnik, Marguerite Burnat-Provins, female erotic poetry, self-insertion poem, Slovenian-French literary contacts